Analysis Self-Expressive, Brand Trust, Hedonic Product And E-Wom On Brand Love Daon Jajar Ecoprint Bontang - Iwan Amir (Cakrawala Repositori IMWI, 2023)
This thesis aims to examine the relationship and analyze between self-expressive, brand trust, hedonic product and e-WOM on brand love of Daon Jajar Ecoprint in Bontang city. A survey was conducted on users of Daon Jajar Ecoprint products which resulted in 51 valid responses. The existence of ewom variables is significantly influenced by brand love variables, while brand love is influenced by self-expressive, hedonic products. This study also shows that brand trust is not supported to have a significant effect on brand love for Daon Jajar Ecoprint consumers. Consumers do not yet fully trust and rely on the existence of Daon Jajar Ecoprint. In this case, brand trust is more influenced by emotional factors than rational and logical aspects. This study contributes to the literature by introducing and analyzing between self-expressive variables, brand trust, hedonic product and e-WOM on Daon Jajar Ecoprint brand love.